2015
DOI: 10.1590/1981-38212015000300021
|View full text |Cite
|
Sign up to set email alerts
|

Assessing some measures of online deliberation

Abstract: The empirical turn in deliberative democracy has fostered the development of different methodological procedures. Within this literature, studies focusing on the internet have gained increasing attention. The belief that the internet may help solve some of the deliberative deficits of democracies has propelled an interest in the potential benefits and problems of online discourse. This article seeks to discuss some of the methods that have been advocated for the study of online deliberation to point out three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Therefore, the DQI reduces assessments of the deliberative quality of reason giving to judgements on 'logical infrastructure or linguistic structure of arguments-an idea that is distant from the concept of communicative rationality underpinning deliberative theories' (Maia et al 2020: 4). As a result, the DQI reduces the potential of interpretation of deliberative quality to be more sensitive to culture (Mendonça 2015). Interpretive approaches to assessing deliberative quality are more suitable for inquiry into the differences and similarities in argumentation (Maia et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the DQI reduces assessments of the deliberative quality of reason giving to judgements on 'logical infrastructure or linguistic structure of arguments-an idea that is distant from the concept of communicative rationality underpinning deliberative theories' (Maia et al 2020: 4). As a result, the DQI reduces the potential of interpretation of deliberative quality to be more sensitive to culture (Mendonça 2015). Interpretive approaches to assessing deliberative quality are more suitable for inquiry into the differences and similarities in argumentation (Maia et al 2020).…”
Section: Methodsmentioning
confidence: 99%
“…It originated from Habermasian discourse ethics and was initially applied to parliamentary debates (Jaramillo and Steiner 2019). While there are criticisms of the DQI method with respect to how well it can be applied to all contexts and the restricted notion of deliberation it adopts (Mendonça 2015;Jaramillo and Steiner 2019), we maintain that these can be overcome by adapting the coding framework. We agree with the original DQI creators that "wherever there is deliberation of some sort and there is a record, the DQI can be applied" (Steenbergen et al 2003, 44).…”
Section: Assessing Deliberative Qualitymentioning
confidence: 99%
“…While acknowledging that a fuller analysis of emotion would require visual and oral analysis of the discussions (Mendonça, Ercan, and Hans 2020), we found that coding of the transcripts in this way still provided useful and reliable data, noting that coders had been present during deliberations. This is the first attempt to expand the DQI to include emotion and to respond to critiques that the method relies on an overly formal conception of deliberation (Mendonça 2015).…”
Section: Assessing Deliberative Qualitymentioning
confidence: 99%
“…Since the path-breaking research of Clark and Brennan, scholars in social science have explored a variety of aspects of online deliberation, including the problem of assessing its “quality” (e.g. Mendonça, 2015). Most of this literature analyzes case studies of online public consultations (e.g.…”
Section: Theoretical Background: Assessing the Cost Of Mediated Convementioning
confidence: 99%